Literacy Practice on Project Bassed Learning (PBL) Assisted by Peer Assessment in Hybrid Learning to Improve the Students' Critical Thinking Ability in Tertiary Level of Education - Aswadi Jaya; Rudi Hartono; Sri Wahyuni; Henrikus Joko Yulianto (International Conference on Science, Education, and Technology, 2023)
The students’ literacy became lower since the hybrid learning also has its weaknesses, namely students feel bored because the learning process is monotonous and less interesting. Thus, the students are not interested in learning and completing learning carried out in e-learning. The aim of this study was to analyze the effect of learningproject-based learning assisted by peer assessment in hybrid learning to improve students' critical thinking skills as the implementation of literacy practices. The study uses the posttest only control group design. The population of this study was all second semester English Education Study Program students in PGRI University of Palembang, totaling 170 students. Descriptive statistical analysis techniques are used to describe the data obtained. The hypothesis testing used is the t-test to test the significant level of the influence of the independent variables partially on the dependent variable. The test is carried out by comparing t-count with t-table. The results of the analysis show that the value of Sig. obtained less than 0.05. This means that there are differences in students' critical thinking skills being taught project-based learning(PBL) assisted by peers with students who are taught without learning project-based learning(PBL) assisted by peers. The implications of this research are that it is hoped that with this learning model students will learn more actively in building their own knowledge as the literacy processes which will have an impact on critical thinking skills.